2014
DOI: 10.1186/1743-422x-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Southern rice black-streaked dwarf virus (SRBSDV) directly affects the feeding and reproduction behavior of its vector, Sogatella furcifera (Horváth) (Hemiptera: Delphacidae)

Abstract: BackgroundSouthern rice black-streaked dwarf virus (SRBSDV) is a recently discovered member of the genus Fijivirus and it is transmitted by the rice whitebacked planthopper (WBPH), Sogatella furcifera (Horváth). It was found that SRBSDV infected vectors might contribute negatively to the WBPH population, although the longer nymphal period might benefit viral acquisition, transmission and increase infection rate. The interaction between SRBSDV and its vector need to be further explored to gain better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Our previous study demonstrated that the WBPH nymph duration as well as the female fecundity and longevity were significantly affected by SRBSDV, either directly (by infection of WBPH) or indirectly (by infection of rice plants) 15 . Other studies reported similar results for the same virus-vector interaction 13 16 .…”
supporting
confidence: 70%
“…Our previous study demonstrated that the WBPH nymph duration as well as the female fecundity and longevity were significantly affected by SRBSDV, either directly (by infection of WBPH) or indirectly (by infection of rice plants) 15 . Other studies reported similar results for the same virus-vector interaction 13 16 .…”
supporting
confidence: 70%
“…Tomato yellow leaf curl virus (TYLCV) infected vectors Bemisia tabaci exhibit a reduced fecundity of approximately 40–50% 14 . Similarly, the white-backed planthopper ( Sogatella furcifera ), the vector of Southern rice black-streaked dwarf virus (SRBSDV), dramatically reduces their oviposition when the parents are infected with SRBSDV 15 16 . However, the vector green leafhopper ( Nephotettix cincticeps ) increased their fecundity when they fed on Rice dwarf virus (RDV)-infected rice plants 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that the persistent propagation of plant viruses adversely affects insect vectors, including prolonging the nymphal stages, shortening adult longevity, reducing survival rate, or decreasing fecundity (22,59,63,77,102,103,123). These adverse changes could be attributed to direct effects of virus-insect interactions or indirect effects of the components from diseased plants.…”
Section: Adverse Effects Of Viral Infectionmentioning
confidence: 99%